Reflections on the Need for Hierarchies in Bioethical Principlism (2018)
This paper presents an analysis of biomedical principlism as proposed by Beauchamp and Childress, establishing non-hierarchical posture based on the four principles of autonomy, beneficence, non-maleficence and justice. It is argued that a hierarchy of principles is needed to establish an ethical foundation, without which medical practice can fall into a relativism that is damaging to the integrity and dignity of patients. Furthermore, it is argued that the strengthening of the autonomy principle would hierarchically privilege opportunities to generate a non-patronizing medical perspective and medical practices commensurate with the defense of primary human right